2022
DOI: 10.1155/2022/9897442
|View full text |Cite
|
Sign up to set email alerts
|

Four-Octyl Itaconate Attenuates UVB-Induced Melanocytes and Keratinocytes Apoptosis by Nrf2 Activation-Dependent ROS Inhibition

Abstract: Vitiligo is an acquired skin depigmentation disease in which excessive reactive oxygen species (ROS) play a critical pathogenic role in melanocyte destruction. The complex crosstalk between melanocytes and keratinocytes in vitiligo suggests that treatments aimed at protecting both the cells might be meaningful. In this study, we investigated the effect of 4-octyl itaconate (4-OI), an itaconate derivative, on ultraviolet B- (UVB-) induced apoptosis in HaCaT and PIG1 cells and the underlying mechanisms. HaCaT an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…By reducing oxidative stress and inflammation, 4-OI inhibited LPS-induced acute lung injury in mice, which was confirmed by the reduced lung tissue damage and inflammatory response [ 53 ]. Furthermore, 4-OI administered through tail-vein injection attenuated UVB-induced skin damage in mice by inhibiting ROS production [ 54 ]. Since ROS are one of the main factors driving islet cell death during hypoxia, we hypothesized that 4-OI could protect MIN6 cells against hypoxic injury through the inhibition of ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…By reducing oxidative stress and inflammation, 4-OI inhibited LPS-induced acute lung injury in mice, which was confirmed by the reduced lung tissue damage and inflammatory response [ 53 ]. Furthermore, 4-OI administered through tail-vein injection attenuated UVB-induced skin damage in mice by inhibiting ROS production [ 54 ]. Since ROS are one of the main factors driving islet cell death during hypoxia, we hypothesized that 4-OI could protect MIN6 cells against hypoxic injury through the inhibition of ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Another study also showed that 4-OI significantly inhibited ROS production by activating Nrf2, which in turn caused downregulation of AMPK phosphorylation levels, and improved free fatty acid-induced oxidative stress and lipid metabolism disorders in hepatocytes [ 43 ]. Itaconate has also attenuated inflammatory damage through activation of Nrf2 in other diseases such as osteoarthritis [ 44 47 ], nerve injury [ 48 , 49 ], cardiovascular disease [ 50 , 51 ], systemic lupus erythematosus [ 52 ], vitiligo [ 53 ], periodontitis [ 54 ], fungal keratitis [ 55 ], and diabetic wound repair [ 56 ]. Consequently, itaconate, as an Nrf2 agonist, may present new therapeutic opportunities for many inflammatory diseases.…”
Section: Immunomodulatory Mechanisms Of Itaconatementioning
confidence: 99%
“…As described in ‘5.2.1 Regulating KEAP1 activity’, itaconate increases the alkylation of cysteine residues 151, 257, 273, 288, and 297 on KEAP1, enhances the degradation of KEAP1 and leads to the dissociation and activation of Nrf2. Bambouskova et al demonstrated that itaconate and DI reacted with glutathione and activated Nrf2 [ 21 ], then in the process of periodontal destruction [ 179 ], liver fibrosis [ 72 ], vitiligo [ 180 ], pulmonary fibrosis [ 181 ], renal injury [ 175 ], osteoporosis [ 182 ], and neurodegenerative diseases [ 183 ], itaconate and its derivatives functioned as activators of the Nrf2 pathway and attenuated oxidative stress. Moreover, Yi et al reported that itaconate activated Nrf2 to mitigate oxidative stress in liver IRI, which demonstrated the antioxidant effect in nonimmune cells [ 163 ].…”
Section: Roles Of Itaconate In Inflammatory and Oxidative Stress-indu...mentioning
confidence: 99%